2019
DOI: 10.1186/s12936-019-2846-3
|View full text |Cite
|
Sign up to set email alerts
|

Malaria infection promotes a selective expression of kinin receptors in murine liver

Abstract: Background Malaria represents a worldwide medical emergency affecting mainly poor areas. Plasmodium parasites during blood stages can release kinins to the extracellular space after internalization of host kininogen inside erythrocytes and these released peptides could represent an important mechanism in liver pathophysiology by activation of calcium signaling pathway in endothelial cells of vertebrate host. Receptors (B1 and B2) activated by kinins peptides are importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…This expression pattern aligns with well-described dominance of NO-based vasodilation in conduit arteries compared to resistance arteries [46]. While B 2 receptors are widely expressed throughout the healthy endothelium [50], B 1 expression is limited to the endothelium of cerebral [57] and hepatic [58] microvessels. Its expression in homeostasis is minimal; however, it is induced following peripheral tissue injury [59], in the presence of the proinflammatory cytokine interferon gamma [57], or following Plasmodium chabaudi infection [58].…”
Section: On the Face Of Flow: Luminal Membranesupporting
confidence: 77%
“…This expression pattern aligns with well-described dominance of NO-based vasodilation in conduit arteries compared to resistance arteries [46]. While B 2 receptors are widely expressed throughout the healthy endothelium [50], B 1 expression is limited to the endothelium of cerebral [57] and hepatic [58] microvessels. Its expression in homeostasis is minimal; however, it is induced following peripheral tissue injury [59], in the presence of the proinflammatory cytokine interferon gamma [57], or following Plasmodium chabaudi infection [58].…”
Section: On the Face Of Flow: Luminal Membranesupporting
confidence: 77%
“…B1R-knockout mice presented a significant reduction of survival when compared with wild-type mice, unlike the B2R-knockout ones (72). In this inflammation/infection model, chloroquineinduced upregulation of B1R expression proved protective: the full meaning of this result is unclear but might indicate that the selective inhibition of B2R could represent a rational modulation of dysregulated BK pathway during infection.…”
Section: The Renin-angiotensin System (Ras) and The Interplay With Kksmentioning
confidence: 74%
“…Finally, it is interesting to observe that in an experimental malaria model ( Plasmodium parasites during blood stages release kinins), exposure to captopril (an ACE-inhibitor that leads to the reduction of BK degradation) resulted in death in mice, while the concomitant administration of chloroquine protected them. B1R-knockout mice presented a significant reduction of survival when compared with wild-type mice, unlike the B2R-knockout ones ( 72 ). In this inflammation/infection model, chloroquine-induced upregulation of B1R expression proved protective: the full meaning of this result is unclear but might indicate that the selective inhibition of B2R could represent a rational modulation of dysregulated BK pathway during infection.…”
Section: The Renin–angiotensin System (Ras) and The Interplay With Kkmentioning
confidence: 85%
“…In an in vivo study, P. chabaudi infection was related to an upregulation of B 1 receptors in endothelial cells of sinusoids and other blood vessels of mouse liver. Of note, the anti-malarial drug chloroquine modulated the expression of B 1 receptors in this tissue [ 168 ]. A clinical study showed the activation of coagulation cascade in severe malaria caused by P. falciparum .…”
Section: Kinins and Their Implication In Protozoan And Parasite Inmentioning
confidence: 99%